Ultrahigh sensitive carbon-based conducting rubbers for flexible and wearable human-machine intelligence sensing - Ajeev, Arya; Javaregowda, Bharathkumar H.; Ali, Ashik; Modak, Mrudul; Patil, Shreya; Khatua, Saumyakanta; Ramadoss, Marimuthu; Kothavade, Premkumar Anil; Arulraj, Arul Kashmir (Advanced Materials Technologies, 2020)
The wearable strain sensors with multifunctional applications can fuel the rapid development of human-machine intelligence for various sectors like healthcare, soft robotics, and Internet of Things applications. However, achieving the low-cost and mass production of wearable sensors with ultra-high performance remains challenging. Herein, a simple, cost-effective, and scalable methodology to fabricate the flexible and highly sensitive strain sensors using carbon black and latex rubbers (LR) is presented. The LR-based strain sensor demonstrates excellent flexibility, fast response (approximate to 600 ms), ultra-high sensitivity (maximum gauge factor of 1.2 x 10(4) at 250% strain), and long-term stability over 1000 cycles. The LR-based strain sensors are sensitive to monitor subtle human motions such as heart pulse rate and voice recognition along with high-strain human joint operations. Additionally, the sensing mechanism of LR bands is investigated by surface topographies and electromechanical response under various strained/unstrained conditions. Further, a smart glove-based sensor module made of LR strain bands with an Arduino reader for the human-machine intelligence device for non-verbal communication in military applications is demonstrated.
Keywords: conducting rubbers; gauge factor; human– machine interfacing; voice recognition; wearable strain sensors